Peningkatan Soft Skill komunitas pemuda melalui Pelatihan Videografi dan Fotografi untuk Pengembangan Kreativitas dan Ekonomi Lokal di Desa Semare Kecamatan Kraton Kabupaten Pasuruan - Machfudi Zulkif, Senjaya; Lujeng Lestari, Isnawati; Syawaludin, Makhfud; Aris Fajarudin, Ahmad (Humanist Journal, 2024)
The videography and photography training in Semare Village aims to enhance the soft skills of the youth community by developing creativity and supporting the local economy. This program provides technical skills in photography and videography, as well as the development of essential soft skills such as communication, teamwork, and creativity. Through this training, the village youth can produce creative products with economic value, such as event documentation and promotional content, which can be marketed to boost the village's economy. This program is expected to open new job opportunities and develop the creative economy in the village, despite challenges related to resource limitations and accessibility for some participants.